Green entrepreneurship capabilities and strategic accounting as dual drivers of MSME sustainability: the moderating dynamics of financial technology adoption - Prasetiyo, Yudhi (Universitas Widya Mataram, 2025)
This study aims to analyze the influence of green entrepreneurial orientation and strategic accounting on business sustainability, with financial technology (Fintech) as a moderating variable. This study uses quantitative approach with an explanatory research type. Data collection was conducted by distributing questionnaires to 100 micro, small, and medium enterprises (MSMEs) in South Tangerang City. The data analysis technique used the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM). The results show that green entrepreneurial orientation and strategic accounting have a direct positive and significant effect on MSME business sustainability. This finding emphasizes the importance of integrating environmental awareness and strategic financial management in building sustainable small and medium enterprises in the modern era. However, the results also show that Fintech as a moderating variable does not have a significant influence in strengthening the relationship between green entrepreneurial orientation and strategic accounting on business sustainability. The research model used has met the validity and reliability indicators and has good predictive power. Based on the results of this study, it’s recommended that MSMEs increase their understanding and capacity in implementing green entrepreneurship principles, strengthen strategic accounting practices, and gradually optimize the use of Fintech to support long term business sustainability.